2003
DOI: 10.1109/tbme.2003.808824
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotocographic recordings

Abstract: Antepartum fetal monitoring based on the classical cardiotocography (CTG) is a noninvasive and simple tool for checking fetal status. Its introduction in the clinical routine limited the occurrence of fetal problems leading to a reduction of the precocious child mortality. Nevertheless, very poor indications on fetal pathologies can be inferred from the even automatic CTG analysis methods, which are actually employed. The feeling is that fetal heart rate (FHR) signals and uterine contractions carry much more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
235
1
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(251 citation statements)
references
References 33 publications
7
235
1
8
Order By: Relevance
“…Some of those indices, previously used by some of us in FHR analysis (Vieira et al 2004, Felgueiras et al 1998, may be useful, as the scaling behaviour of HR seems to be selectively related to the alpha-adrenergic activity whereas entropy appears to be related to cholinergic activity (Beckers et al 2006b). Those indices were outside the scope of this study, which was designed, like our last series of studies on FHR (Gonçalves et al 2006a(Gonçalves et al , 2006b(Gonçalves et al , 2007, to be more comparable with other FHR studies published in the literature (Magenes et al 2000, Signorini et al 2003. On the other hand, in this study an evaluation of entropy was performed in more depth than in other studies.…”
Section: Discussionmentioning
confidence: 88%
“…Some of those indices, previously used by some of us in FHR analysis (Vieira et al 2004, Felgueiras et al 1998, may be useful, as the scaling behaviour of HR seems to be selectively related to the alpha-adrenergic activity whereas entropy appears to be related to cholinergic activity (Beckers et al 2006b). Those indices were outside the scope of this study, which was designed, like our last series of studies on FHR (Gonçalves et al 2006a(Gonçalves et al , 2006b(Gonçalves et al , 2007, to be more comparable with other FHR studies published in the literature (Magenes et al 2000, Signorini et al 2003. On the other hand, in this study an evaluation of entropy was performed in more depth than in other studies.…”
Section: Discussionmentioning
confidence: 88%
“…More details can be found in [17]. -Combined model: Combined valve timing and FHRrelated parameters.…”
Section: Estimation Of the Gestational Agementioning
confidence: 99%
“…ApEn has been introduced in based on the theory that human well-being is associated to an high level of irregularity of biomedical time series (e.g. heart rate, respiratory acidosis, and dynamics of hormone release) (Signorini et al 2003;Xiaotian et al 2005;Ferrario et al 2006). We found that the mean value of ApEn showed a slight negative correlation with gestational age.…”
Section: Discussionmentioning
confidence: 63%
“…The middle frequency (MF 0.15-0.5 Hz) depends on foetal movements and maternal breathing activity and it is typical of FHR spectrum. LF/ (HF þ MF) ratio quantifies the autonomic balance between neural control mechanisms from different origin (Signorini et al 2003).…”
Section: Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation